Response to Chemotherapy in Overweight/Obese Patients With Low-Risk Gestational Trophoblastic Neoplasia - Maesta, Izildinha [UNESP]; Horowitz, Neil S.; Goldstein, Donald P.; Bernstein, Marilyn R.; Ramirez, Luz Angela C. [UNESP]; Moulder, Janelle; Berkowitz, Ross S. (Lippincott Williams &wilkins, 2015)
Objective Despite rising global obesity rates, the impact of obesity on gestational trophoblastic neoplasia (GTN) remains uninvestigated. This study aimed at investigating whether overweight/obesity relates to response to chemotherapy in low-risk GTN patients.Methods This nonconcurrent cohort study included 300 patients with International Federation of Gynecology and Obstetrics-defined postmolar low-risk GTN treated with a single-agent chemotherapymethotrexate or actinomycin-D (actD)between 1973 and 2012 at the New England Trophoblastic Disease Center. Chemotherapy dosing was based on actual body weight regardless of obesity status, except for 5-day courses or pulse regimens of actD. Patients were classified as overweight/obese (body mass index [BMI] 25 kg/m(2)) or non-overweight/obese (BMI <25 kg/m(2)). Information on patient characteristics and response to chemotherapy (need for second-line chemotherapy, reason for changing to an alternative chemotherapy, number of cycles, need for combination chemotherapy, and time to human chorionic gonadotropin remission) was obtained.Results Of 300 low-risk GTN patients, 81 (27%) were overweight/obese. Overweight/obese patients were older than the non-overweight/obese patients (median age: 30 vs 28 years, P = 0.004). First-line therapy using actD was more frequent in overweight/obese patients (6.2% vs 1.4%, P = 0.036). Resistance and toxicity were similar between groups. No significant difference in the number of chemotherapy cycles needed for remission or time required to achieve remission was found between groups.Conclusions No association between overweight/obesity and low-risk GTN outcomes was found. Current chemotherapy dosing using BMI seems to be appropriate for overweight/obese patients with low-risk GTN.
Keywords: Low-risk gestational trophoblastic neoplasia; Overweight; obesity; Chemotherapy; Outcomes